History teaching in Russia and Ukraine: the revision of school textbooks in a comparative perspective (1991-2014) - Caroli, Dorena (Rivista di Storia dell’Educazione, 2023)
This article aims at presenting some relevant aspects of the heated historiographical debate on the evolution of the teaching of history and on the revision of textbooks performed in post-Soviet Russia and Ukraine. The introduction will describe the beginning of the renewal process of history teaching undertaken in the years preceding the fall of the communist regime (December 1991). The first part and the second one will analyse the main features of the textbooks revision process in the two countries, Russia and Ukraine, after 1991, focusing on the most popular textbooks and interpretation changes in the textbooks published after 2000. The Russian invasion of Ukraine was the culmination of a process of geopolitical instrumentalization of history that led to the separation of the history shared between the two countries.